TEORÍAS GEOPOLÍTICAS - Giudice Baca, Victor (2005)
The present study exposes six geopolitical theories belonging to Alfred Mahamçn, Halford Mackinder, James Fairgrieve, Nicolas Spykman, Alexander Seversky and Samuel Cohen. It is considered that the Theory of the Marine Power of Mahan (1890) was enlarged by the Theory of the Terrestrial Power of Mackinder (1905). James Fairgrieve (1915) designed a world based on Areas of Pressure, Areas of Conflict and Countries Buffer or countries designed to separate to each other to the big powers. Nepal from the India, Finland of the Nordic Countries, Belgium separated the vicinity from Germany to England and north flank of France. The theory of the Air Power (Seversky 1959) was born before the rupture of the marine and terrestrial blockades for the Soviet aviation. Samuel Cohen (USA, 1990 and 2002) created the Theory of the Hierarchy of the appropriate Global Sapces for a tripolar world constituted by the United States, the European Union of 25 countries and the Pacific (Russia, China, Japan) . Spykman (USA, 1950) established the Theory of the Perimeter of Security of the United States.